No rescaldo da escravatura. As ciências sociais chamadas à liça nos anos 30 (século XX) - Santos, Maria Emília Madeira; Rodrigues, Vítor (Africana Studia, 2020)
The need to stop prolonged situations of slavery or re-enactments of slavery situations had led the Sociedade das Nações to the creation, in 1922, of the “Comissão Temporária de Escravatura”. Ten years later, because it was urgent to evaluate, in a scientific way, the results of its performance in the colonial powers, as well as its effect in the populations, the colonial politicians in charge called in a large group of researchers from several domains of knowledge. Portugal, following the example of Belgium, attributed to a set of specialists in colonial affairs the task of elaborating a “Ethnographic Questionnaire on Slavery” that, on one side, intended to evaluate the real state of the problem of slavery and its “analogue forms” in the colonies, and, on the other side, was meant to caution the colonial politics developed by the Portuguese state. The analysis of its action and the political setting in which it occurred, will be the main object of our work that sets the starting point for a wider study of this problem.